SEMANTIC REINTERPRETATION OF THE PROPHET MUHAMMAD’S OBLIGATORY PROPERTIES FOR DA’WAH ADVANCEMENT IN THE INTER-RELIGIOUS CONTEXT - Abdullah Muslich Rizal Maulana (Jurnal MD, 2018)
A further improvement is necessary for the advancement of da’wah in the context of interreligious communities. Regarding the growing of this demand Muslim should evaluate their da’wah method. This paper will attempt to reformulate the method of da’wah based on semantic analysis toward the four obligatory properties of Prophet Muhammad siddiq, amanah, tabligh, and fatanah. Research question here is how we should redefine the obligatory properties of Prophet Muhammad via semantic theoretical framework for the advancement of da’wah in the interreligious context.  To achieve this goal, I will put several sub-chapters to discuss the semantic theoretical framework, namely: the relationship with the Islamic worldview, the elaboration of the compulsory nature of the Prophet Muhammad through the semantic theoretical framework, and then end by overcoming the analysis with a new form of da’wah that anticipates the interfaith context late in inter-commitment from the Islamic truth. This paper concludes that redefining the obligatory properties of Prophet Muhammad via semantic theoretical framework derives the inter-commitment of the Islamic truth as the theological foundation of da’wah in the late interreligious context. It entails the deeper reflection of siddiq, amanah, tabligh, and fatanah the direction of intensifying the competence of da’i regarding the advancement of da’wah in the recent interreligious context.